Traditional Food Heritage in Contemporary Tuscany: Local Networks and Global Policies around the Zolfino Bean - Badii, Michela (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2013)
This article aims to explore the creation of a heritage in traditional food in contemporary Tuscany. For this purpose, we will analyse the “social life” developing around the zolfino bean, a product which is a symbol of local tradition. The main subjects of the study are observed during their everyday lives in the local context in order to identify food heritage policies as well as the subjectivization processes emerging from below. In particular, we will look at the “battle” for labelling which highlights the controversial line between localisation and globalisation. This case study reveals the ambiguous nature of heritage policies which transform local capital into goods embodying a sense of “belonging to the territory” in terms of social access and lifestyle.